A Self-generated Chemotaxis-inspired routing method for digital microfluidic cooling of hotspots in integrated circuits. (15th August 2022) - Chen, Maohua; Chen, Senlong; Liao, Ming; Jin, Mingliang; Zhao, Yugang; Zhou, Guofu; Shui, Lingling; Yan, Zhibin
Highlights: Inspired by chemotaxis, droplet can search for hot spots based on thermal gradient. A bio-inspired droplet routing method for digital microfluidic cooling is proposed. Cooling performance of the routing method enhances with increasing inlet count. Compared with ant colony algorithm, the proposed method can ease target conflict. Abstract: Effective thermal management is of great significance for the reliability of the high-density-power electronics such as the three-dimensional integrated circuits (3DICs). Cooling method based on digital microfluidic (DMF) driven by electrowetting-on-dielectric (EWOD) has been regarded as a promising solution to the effective thermal management of 3DICs. Compared with other traditional cooling methods, DMF has advantages of lower power consumption and especially adaptive cooling ability which can achieve accurate cooling for hot spots inside the 3DICs. However, there are hardly any researches investigating into the droplet routing methods for DMF cooling systems. In this paper, we propose a droplet route optimization method inspired by the self-generated chemotaxis which aims to achieve real-time and parallel routing for multiple coolant droplets to search and cool hot spots. Based on the proposed thermal model of integrated circuit and DMF cooling system, various cooling cases have been simulated with different configurations (e.g., the cooling route and the inlet number). Numerical results show that the proposed self-generated chemotaxis-inspired algorithm (SCA) is capable of searching multiple hot spots based on the real-time temperature profiles and realizing multiple droplets routing simultaneously (i.e., parallel routing and cooling). Compared with traditional ant-colony-algorithm route and direct route, the SCA route provides the best temperature mitigation performance in appropriate inlet-configuration, and its cooling performance can be further improved as the inlet number increases.